Improvement of aquaculture management practice by integration of hydrodynamic modelling. (1st November 2021) - Urke, H.A.; Daae, K.; Viljugrein, H.; Kandal, I.; Staalstrøm, A.; Jansen, P.A.
Abstract: Aquaculture has grown to become an important export industry in Norway. The Norwegian Food Safety Authorithy (NFSA) is responsible for the management of the production zones designated to aquaculture. Fish diseases and fish parasites are among the main threats to the aquaculture industry. It is therefore of great interest to minimize the risk of fish disease agent transmission. To date, the NFSA has assigned specific subzone divisions for aquaculture installations without assessing the effects of water contact for larger areas. Transmission of infection by water contact is believed to predominate the dispersal of important fish pathogens such as salmon pancreas disease virus (SPDV), infectious salmon anaemia (ISA) virus, Aeromonas salmonicida bacterias (held efficiently under control now by effective vaccines and not a major problem), and salmon lice. In this article we present a three-dimensional hydrodynamic model system (AquaStrøm) which gives detailed information about a network of 48 fish farm sites with varying degrees of mutual water contact in a Norwegian fjord area (the Nordfjord). By adding information on winds and currents, a better understanding of the mechanisms for the risk of transmission of fish disease agent between fish farms is gained. The risk of infection can be assessed in much more detail, and the production zones can be designed and optimized based on the level of water contact between various clusters of fish farms. Key sites which connect clusters of fish farms and hence increase the areas of mutual water contact can be identified. Graphical abstract: The productions zones for fish farm sites (circles) used by the authorities (upper panel) and the zones based on a high degree of water contact between the sites (lower panel). Different coloured circles represent sites in different zones. Image 1 Highlights: The model gives detailed information about the water contact between fish farms. Key sites which connect clusters of fish farms can be identified and evaluated. Optimize production zones by reducing the risk of spreading infection and diseases.